1999
DOI: 10.1103/physrevb.59.1223
|View full text |Cite
|
Sign up to set email alerts
|

Surface-induced low-field instability of antiferromagnetic multilayers

Abstract: We discuss the surface-induced low-field instability of the antiferromagnetic phase of magnetic multilayers. The threshold field is calculated analytically for multilayers of arbitrary thickness containing an even number of layers. We show that the threshold is given by H SSF ϭͱH e H a ϩH a 2 , where H e and H a are the effective exchange and anisotropy fields. The effective anisotropy field H a may include both uniaxial and fourfold crystalline anisotropy. Numerical simulations of the equilibrium phases, base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
28
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…The critical field for instability of the AF order in finite multilayers has been calculated analytically, combining the simultaneous effect of uniaxial and four-fold crystalline anisotropy of the F layers. It was shown that the relative orientation of the anisotropy easy directions may affect the nature of the low field phase transition [8]. However, for finite multilayers [5,7,8] where H E and H A are the effective interlayer exchange field and the anisotropy field, in agreement with the prediction in the semi-infinite geometry [4].…”
mentioning
confidence: 71%
See 4 more Smart Citations
“…The critical field for instability of the AF order in finite multilayers has been calculated analytically, combining the simultaneous effect of uniaxial and four-fold crystalline anisotropy of the F layers. It was shown that the relative orientation of the anisotropy easy directions may affect the nature of the low field phase transition [8]. However, for finite multilayers [5,7,8] where H E and H A are the effective interlayer exchange field and the anisotropy field, in agreement with the prediction in the semi-infinite geometry [4].…”
mentioning
confidence: 71%
“…where for the two choices of m z mentioned above, we have used aZ bðHhC a 1 bC 1=2Þ; bZKb/2 and cZ ðGhC a 2 C b=2Þ: Notice that M 4 has the same structure of the corresponding matrix used in the study of the stability of AF multilayers [8], with a redefinition of the parameters a, b and c for the ferrimagnetic case. From the structure of M 4 , it is clear how to obtain M 2 and also how to proceed in order to obtain matrices for larger values of N. All the algebraic manipulations used previously [8] to determine the critical field which produces instability of the AF order of AF multilayers are also valid for ferrimagnetic multilayers.…”
mentioning
confidence: 97%
See 3 more Smart Citations